STRUCTURAL AND STRATEGIC ASPECTS OF PROFESSIONALLY ORIENTED SPEECH OF A PSYCHOLOGIST MEDIATOR - Iryna Levchyk (Ternopil Volodymyr Hnatiuk National Pedagogical University, 2016)
The article presents characteristic speech patterns of psychologist-mediator on the basis of five staged model of his professional speech behavior that involves the following five speech activities: introductory talks with the conflict parties; clarifying of the parties' positions; finding the optimal solution to the problem; persuasion in the legality of a compromise; execution of the agreement between the parties. Each of these stages of the mediation process in terms of mental and speech activities of a specialist have been analyzed and subsequently the structure of mediator's communication has been derived. The concept of a "strategy of verbal behavior" considering professional activity of a psychologist-mediator has been described in terms of its correlation with the type of negotiation behaviors of disputants. The basic types of opponents' behavior in negotiations ‒ namely avoidance, concession, denial, aggression have been specified. The compliance of strategy of speech of mediator's behavior to his chosen style of mediation has been discovered. The tactics and logic of mediator's speech behavior according to the stages of mediation conversation have been determined. It has been found out that the mediator's tactics implies application of specific professional speech skills to conduct a dialogue in accordance with the chosen strategy as well as emotional and verbal reaction of conflict sides in the process of communication.